Ebola virus: an introduction and its pathology. (12th November 2015) - Singh, Gurpreet; Kumar, Arbind; Singh, Kashmir; Kaur, Jagdeep
Summary: The Ebola viruses are causative agent of a severe Ebola virus disease (EVD) or Ebola hemorrhagic fever (EHF) in human and other primates. Transmission of EVD occurs through the contact of body fluids from infected persons or animals, making it one of the most epidemic diseases worldwide. Underestimating the Ebola virus has cost loss of precious human lives in recent years. Ebola virus outbreak in year 2014 created a history, affecting a larger population in a wide geographical region of African sub‐continent. EVD outbreaks have a case fatality rate of up to 70%. Ebola viruses are endemic in regions of Africa. Ebola viruses mainly target the hepatocytes, endothelial, and macrophage‐rich lymphoid tissues and are characterized by immune suppression and a systemic inflammatory response that causes impairment of the vascular, coagulation, and immune systems. This impairment leads to multifocal necrosis and multi organ failure, and thus, in some ways, resembling septic shock. Currently, neither a specific treatment nor a vaccine licensed for use in humans is available. This review is focused on general characteristic of Ebola viruses, its pathogenesis, immunological response of host, and recent approaches for vaccine development against EVD. Copyright © 2015 John Wiley & Sons, Ltd.